2011
DOI: 10.1111/j.1600-0587.2011.06763.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation determines patterns of species presence in highly fragmented landscapes

Abstract: In fragmented landscapes, changes in habitat availability, patch size, shape and isolation may affect survival of local populations. Proposing efficient conservation strategies for such species relies initially on distinguishing the particular effects of those factors. To address these issues, we investigated the occurrence of 3 bird species in fragmented Brazilian Atlantic Forest landscapes. Playback techniques were used to collect presence/absence data of these species inside 80 forest patches, and incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 86 publications
0
57
0
10
Order By: Relevance
“…Therefore, approaches that consider both local forests as well as the whole regional set of patches as the sampling units (i.e. the landscapes) tend to provide better insights on the effects of landscape change on biological populations and communities (Boscolo and Metzger 2011). Recent habitat fragmentation research showed the possibility of buffering effects among scales, regulating the biotic responses to landscape structure in a top-bottom system (see, Pardini et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, approaches that consider both local forests as well as the whole regional set of patches as the sampling units (i.e. the landscapes) tend to provide better insights on the effects of landscape change on biological populations and communities (Boscolo and Metzger 2011). Recent habitat fragmentation research showed the possibility of buffering effects among scales, regulating the biotic responses to landscape structure in a top-bottom system (see, Pardini et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such narrow-ranging studies may miss landscape effects which are only detectable at wider scales. Since single patches within highly fragmented landscapes will hardly support viable populations on their own (Boscolo and Metzger 2011). Ignoring the influence of the quantity or quality of surrounding habitat can compromise the understanding of regional extinction processes.…”
Section: Introductionmentioning
confidence: 99%
“…We recommend vegetation rearrangement to enlarge the smaller patches and enhance their core areas and to patches (Boscolo & Metzger 2011), therefore ensuring a more permeable landscape (Ribeiro et al 2009). If patches smaller than 10 ha were removed from the study landscape, approximately 90% of the remaining patches would be lost.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to Boscolo & Metzger (2011) the mean patch isolation value was low. The former authors showed that less forested landscapes present higher mean isolation when compared to more forested ones.…”
Section: Landscape Analysis For Current and Management Scenariosmentioning
confidence: 99%
“…Besides, these fragments are important elements for maintaining connectivity within each sub-region, since their removal would result in the break-up of the largest sub-graphs (Saura & Pascual-Hortal 2007). The conservation of these fragments (e.g., as private reserves) would be essential to maintain the flux of organisms in the landscape, reducing the isolation of larger fragments (Boscolo & Metzger, 2011).…”
Section: Discussionmentioning
confidence: 99%